The equality of opportunities in the access of higher education - Freire, Ma. Jesus (Education Policy Analysis Archives, 2000)
This work analyzes equality of access to the university in Galicia (Spain) as it was influenced by the political decision to finance higher education at between 80% and 85% of its real cost. The composition of the student body with respect to the level of their parents' education is examined. The analysis confirms that in spite of the significant effort at public financing, the objective of equal access will not be reached.